9514 1404 393
Answer:
y = -x^2 +3x -4
Explanation:
We are given two points with the same y-value, so we know the axis of symmetry lies halfway between their x-coordinates, at ...
x = (1 +2)/2 = 3/2
Then the vertex form of the equation can be written ...
y = a(x -3/2)^2 +k
__
We can use two of the points to find the values of 'a' and 'k'.
For (x, y) = (1, -2)
-2 = a(1 -3/2)^2 +k = a/4 +k
For (x, y) = (3, -4)
-4 = a(3 -3/2)^2 +k = 9a/4 +k
Subtracting the first of these equations from the second, we have ...
(9a/4 +k) -(a/4 +k) = (-4) -(-2)
2a = -2
a = -1
Then k can be found from the first equation.
-2 = -1/4 +k
k = -1 3/4
So, the vertex form equation is ...
y = -(x -3/2)^2 -7/4
__
Expanding this, we can find the standard form.
y = -(x^2 -3x +9/4) -7/4)
y = -x^2 +3x -4